RESTORATIVE JUSTICE DI HUKUM INDONESIA: MENUJU SISTEM PERADILAN YANG LEBIH HUMANIS DAN EFEKTIF - Brahmana, Elva Auryn Ekinteta Br S (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This essay discusses the concept of Restorative Justice within the criminal justice system in Indonesia, which aims to address the limitations of traditional retributive approaches. Restorative Justice emphasizes the restoration of relationships between offenders, victims, and the community, as well as the repair of harm suffered by victims. Although it has gained more serious attention in policies and regulations, the implementation of Restorative Justice in Indonesia still faces various challenges, including a lack of understanding among law enforcement officials and cultural resistance. This article also provides recommendations for further development of Restorative Justice, including enhancing education for law enforcement, public campaigns, and psychological support for victims. By applying the principles of Restorative Justice, it is hoped that the criminal justice system in Indonesia can become more humane and effective.